Mercurial > hg > Members > kono > Proof > galois
comparison src/nat.agda @ 255:6d1619d9f880
library
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Sat, 09 Jan 2021 10:18:08 +0900 |
parents | nat.agda@2eb62a2a34f2 |
children | 891869ead775 |
comparison
equal
deleted
inserted
replaced
254:a5b3061f15ee | 255:6d1619d9f880 |
---|---|
1 {-# OPTIONS --allow-unsolved-metas #-} | |
2 module nat where | |
3 | |
4 open import Data.Nat | |
5 open import Data.Nat.Properties | |
6 open import Data.Empty | |
7 open import Relation.Nullary | |
8 open import Relation.Binary.PropositionalEquality | |
9 open import Relation.Binary.Core | |
10 open import Relation.Binary.Definitions | |
11 open import logic | |
12 | |
13 | |
14 nat-<> : { x y : ℕ } → x < y → y < x → ⊥ | |
15 nat-<> (s≤s x<y) (s≤s y<x) = nat-<> x<y y<x | |
16 | |
17 nat-≤> : { x y : ℕ } → x ≤ y → y < x → ⊥ | |
18 nat-≤> (s≤s x<y) (s≤s y<x) = nat-≤> x<y y<x | |
19 | |
20 nat-<≡ : { x : ℕ } → x < x → ⊥ | |
21 nat-<≡ (s≤s lt) = nat-<≡ lt | |
22 | |
23 nat-≡< : { x y : ℕ } → x ≡ y → x < y → ⊥ | |
24 nat-≡< refl lt = nat-<≡ lt | |
25 | |
26 ¬a≤a : {la : ℕ} → suc la ≤ la → ⊥ | |
27 ¬a≤a (s≤s lt) = ¬a≤a lt | |
28 | |
29 a<sa : {la : ℕ} → la < suc la | |
30 a<sa {zero} = s≤s z≤n | |
31 a<sa {suc la} = s≤s a<sa | |
32 | |
33 refl-≤s : {x : ℕ } → x ≤ suc x | |
34 refl-≤s {zero} = z≤n | |
35 refl-≤s {suc x} = s≤s (refl-≤s {x}) | |
36 | |
37 a≤sa : {x : ℕ } → x ≤ suc x | |
38 a≤sa {zero} = z≤n | |
39 a≤sa {suc x} = s≤s (a≤sa {x}) | |
40 | |
41 =→¬< : {x : ℕ } → ¬ ( x < x ) | |
42 =→¬< {zero} () | |
43 =→¬< {suc x} (s≤s lt) = =→¬< lt | |
44 | |
45 >→¬< : {x y : ℕ } → (x < y ) → ¬ ( y < x ) | |
46 >→¬< (s≤s x<y) (s≤s y<x) = >→¬< x<y y<x | |
47 | |
48 <-∨ : { x y : ℕ } → x < suc y → ( (x ≡ y ) ∨ (x < y) ) | |
49 <-∨ {zero} {zero} (s≤s z≤n) = case1 refl | |
50 <-∨ {zero} {suc y} (s≤s lt) = case2 (s≤s z≤n) | |
51 <-∨ {suc x} {zero} (s≤s ()) | |
52 <-∨ {suc x} {suc y} (s≤s lt) with <-∨ {x} {y} lt | |
53 <-∨ {suc x} {suc y} (s≤s lt) | case1 eq = case1 (cong (λ k → suc k ) eq) | |
54 <-∨ {suc x} {suc y} (s≤s lt) | case2 lt1 = case2 (s≤s lt1) | |
55 | |
56 n≤n : (n : ℕ) → n Data.Nat.≤ n | |
57 n≤n zero = z≤n | |
58 n≤n (suc n) = s≤s (n≤n n) | |
59 | |
60 <→m≤n : {m n : ℕ} → m < n → m Data.Nat.≤ n | |
61 <→m≤n {zero} lt = z≤n | |
62 <→m≤n {suc m} {zero} () | |
63 <→m≤n {suc m} {suc n} (s≤s lt) = s≤s (<→m≤n lt) | |
64 | |
65 max : (x y : ℕ) → ℕ | |
66 max zero zero = zero | |
67 max zero (suc x) = (suc x) | |
68 max (suc x) zero = (suc x) | |
69 max (suc x) (suc y) = suc ( max x y ) | |
70 | |
71 -- _*_ : ℕ → ℕ → ℕ | |
72 -- _*_ zero _ = zero | |
73 -- _*_ (suc n) m = m + ( n * m ) | |
74 | |
75 exp : ℕ → ℕ → ℕ | |
76 exp _ zero = 1 | |
77 exp n (suc m) = n * ( exp n m ) | |
78 | |
79 minus : (a b : ℕ ) → ℕ | |
80 minus a zero = a | |
81 minus zero (suc b) = zero | |
82 minus (suc a) (suc b) = minus a b | |
83 | |
84 _-_ = minus | |
85 | |
86 m+= : {i j m : ℕ } → m + i ≡ m + j → i ≡ j | |
87 m+= {i} {j} {zero} refl = refl | |
88 m+= {i} {j} {suc m} eq = m+= {i} {j} {m} ( cong (λ k → pred k ) eq ) | |
89 | |
90 +m= : {i j m : ℕ } → i + m ≡ j + m → i ≡ j | |
91 +m= {i} {j} {m} eq = m+= ( subst₂ (λ j k → j ≡ k ) (+-comm i _ ) (+-comm j _ ) eq ) | |
92 | |
93 less-1 : { n m : ℕ } → suc n < m → n < m | |
94 less-1 {zero} {suc (suc _)} (s≤s (s≤s z≤n)) = s≤s z≤n | |
95 less-1 {suc n} {suc m} (s≤s lt) = s≤s (less-1 {n} {m} lt) | |
96 | |
97 sa=b→a<b : { n m : ℕ } → suc n ≡ m → n < m | |
98 sa=b→a<b {0} {suc zero} refl = s≤s z≤n | |
99 sa=b→a<b {suc n} {suc (suc n)} refl = s≤s (sa=b→a<b refl) | |
100 | |
101 minus+n : {x y : ℕ } → suc x > y → minus x y + y ≡ x | |
102 minus+n {x} {zero} _ = trans (sym (+-comm zero _ )) refl | |
103 minus+n {zero} {suc y} (s≤s ()) | |
104 minus+n {suc x} {suc y} (s≤s lt) = begin | |
105 minus (suc x) (suc y) + suc y | |
106 ≡⟨ +-comm _ (suc y) ⟩ | |
107 suc y + minus x y | |
108 ≡⟨ cong ( λ k → suc k ) ( | |
109 begin | |
110 y + minus x y | |
111 ≡⟨ +-comm y _ ⟩ | |
112 minus x y + y | |
113 ≡⟨ minus+n {x} {y} lt ⟩ | |
114 x | |
115 ∎ | |
116 ) ⟩ | |
117 suc x | |
118 ∎ where open ≡-Reasoning | |
119 | |
120 sn-m=sn-m : {m n : ℕ } → m ≤ n → suc n - m ≡ suc ( n - m ) | |
121 sn-m=sn-m {0} {n} z≤n = refl | |
122 sn-m=sn-m {suc m} {suc n} (s≤s m<n) = sn-m=sn-m m<n | |
123 | |
124 si-sn=i-n : {i n : ℕ } → n < i → suc (i - suc n) ≡ (i - n) | |
125 si-sn=i-n {i} {n} n<i = begin | |
126 suc (i - suc n) ≡⟨ sym (sn-m=sn-m n<i ) ⟩ | |
127 suc i - suc n ≡⟨⟩ | |
128 i - n | |
129 ∎ where | |
130 open ≡-Reasoning | |
131 | |
132 n-m<n : (n m : ℕ ) → n - m ≤ n | |
133 n-m<n zero zero = z≤n | |
134 n-m<n (suc n) zero = s≤s (n-m<n n zero) | |
135 n-m<n zero (suc m) = z≤n | |
136 n-m<n (suc n) (suc m) = ≤-trans (n-m<n n m ) refl-≤s | |
137 | |
138 n-n-m=m : {m n : ℕ } → m ≤ n → m ≡ (n - (n - m)) | |
139 n-n-m=m {0} {zero} z≤n = refl | |
140 n-n-m=m {0} {suc n} z≤n = n-n-m=m {0} {n} z≤n | |
141 n-n-m=m {suc m} {suc n} (s≤s m≤n) = sym ( begin | |
142 suc n - ( n - m ) ≡⟨ sn-m=sn-m (n-m<n n m) ⟩ | |
143 suc (n - ( n - m )) ≡⟨ cong (λ k → suc k ) (sym (n-n-m=m m≤n)) ⟩ | |
144 suc m | |
145 ∎ ) where | |
146 open ≡-Reasoning | |
147 | |
148 0<s : {x : ℕ } → zero < suc x | |
149 0<s {_} = s≤s z≤n | |
150 | |
151 <-minus-0 : {x y z : ℕ } → z + x < z + y → x < y | |
152 <-minus-0 {x} {suc _} {zero} lt = lt | |
153 <-minus-0 {x} {y} {suc z} (s≤s lt) = <-minus-0 {x} {y} {z} lt | |
154 | |
155 <-minus : {x y z : ℕ } → x + z < y + z → x < y | |
156 <-minus {x} {y} {z} lt = <-minus-0 ( subst₂ ( λ j k → j < k ) (+-comm x _) (+-comm y _ ) lt ) | |
157 | |
158 x≤x+y : {z y : ℕ } → z ≤ z + y | |
159 x≤x+y {zero} {y} = z≤n | |
160 x≤x+y {suc z} {y} = s≤s (x≤x+y {z} {y}) | |
161 | |
162 <-plus : {x y z : ℕ } → x < y → x + z < y + z | |
163 <-plus {zero} {suc y} {z} (s≤s z≤n) = s≤s (subst (λ k → z ≤ k ) (+-comm z _ ) x≤x+y ) | |
164 <-plus {suc x} {suc y} {z} (s≤s lt) = s≤s (<-plus {x} {y} {z} lt) | |
165 | |
166 <-plus-0 : {x y z : ℕ } → x < y → z + x < z + y | |
167 <-plus-0 {x} {y} {z} lt = subst₂ (λ j k → j < k ) (+-comm _ z) (+-comm _ z) ( <-plus {x} {y} {z} lt ) | |
168 | |
169 ≤-plus : {x y z : ℕ } → x ≤ y → x + z ≤ y + z | |
170 ≤-plus {0} {y} {zero} z≤n = z≤n | |
171 ≤-plus {0} {y} {suc z} z≤n = subst (λ k → z < k ) (+-comm _ y ) x≤x+y | |
172 ≤-plus {suc x} {suc y} {z} (s≤s lt) = s≤s ( ≤-plus {x} {y} {z} lt ) | |
173 | |
174 ≤-plus-0 : {x y z : ℕ } → x ≤ y → z + x ≤ z + y | |
175 ≤-plus-0 {x} {y} {zero} lt = lt | |
176 ≤-plus-0 {x} {y} {suc z} lt = s≤s ( ≤-plus-0 {x} {y} {z} lt ) | |
177 | |
178 x+y<z→x<z : {x y z : ℕ } → x + y < z → x < z | |
179 x+y<z→x<z {zero} {y} {suc z} (s≤s lt1) = s≤s z≤n | |
180 x+y<z→x<z {suc x} {y} {suc z} (s≤s lt1) = s≤s ( x+y<z→x<z {x} {y} {z} lt1 ) | |
181 | |
182 *≤ : {x y z : ℕ } → x ≤ y → x * z ≤ y * z | |
183 *≤ lt = *-mono-≤ lt ≤-refl | |
184 | |
185 *< : {x y z : ℕ } → x < y → x * suc z < y * suc z | |
186 *< {zero} {suc y} lt = s≤s z≤n | |
187 *< {suc x} {suc y} (s≤s lt) = <-plus-0 (*< lt) | |
188 | |
189 <to<s : {x y : ℕ } → x < y → x < suc y | |
190 <to<s {zero} {suc y} (s≤s lt) = s≤s z≤n | |
191 <to<s {suc x} {suc y} (s≤s lt) = s≤s (<to<s {x} {y} lt) | |
192 | |
193 <tos<s : {x y : ℕ } → x < y → suc x < suc y | |
194 <tos<s {zero} {suc y} (s≤s z≤n) = s≤s (s≤s z≤n) | |
195 <tos<s {suc x} {suc y} (s≤s lt) = s≤s (<tos<s {x} {y} lt) | |
196 | |
197 ≤to< : {x y : ℕ } → x < y → x ≤ y | |
198 ≤to< {zero} {suc y} (s≤s z≤n) = z≤n | |
199 ≤to< {suc x} {suc y} (s≤s lt) = s≤s (≤to< {x} {y} lt) | |
200 | |
201 x<y→≤ : {x y : ℕ } → x < y → x ≤ suc y | |
202 x<y→≤ {zero} {.(suc _)} (s≤s z≤n) = z≤n | |
203 x<y→≤ {suc x} {suc y} (s≤s lt) = s≤s (x<y→≤ {x} {y} lt) | |
204 | |
205 open import Data.Product | |
206 | |
207 minus<=0 : {x y : ℕ } → x ≤ y → minus x y ≡ 0 | |
208 minus<=0 {0} {zero} z≤n = refl | |
209 minus<=0 {0} {suc y} z≤n = refl | |
210 minus<=0 {suc x} {suc y} (s≤s le) = minus<=0 {x} {y} le | |
211 | |
212 minus>0 : {x y : ℕ } → x < y → 0 < minus y x | |
213 minus>0 {zero} {suc _} (s≤s z≤n) = s≤s z≤n | |
214 minus>0 {suc x} {suc y} (s≤s lt) = minus>0 {x} {y} lt | |
215 | |
216 distr-minus-* : {x y z : ℕ } → (minus x y) * z ≡ minus (x * z) (y * z) | |
217 distr-minus-* {x} {zero} {z} = refl | |
218 distr-minus-* {x} {suc y} {z} with <-cmp x y | |
219 distr-minus-* {x} {suc y} {z} | tri< a ¬b ¬c = begin | |
220 minus x (suc y) * z | |
221 ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} (x<y→≤ a)) ⟩ | |
222 0 * z | |
223 ≡⟨ sym (minus<=0 {x * z} {z + y * z} le ) ⟩ | |
224 minus (x * z) (z + y * z) | |
225 ∎ where | |
226 open ≡-Reasoning | |
227 le : x * z ≤ z + y * z | |
228 le = ≤-trans lemma (subst (λ k → y * z ≤ k ) (+-comm _ z ) (x≤x+y {y * z} {z} ) ) where | |
229 lemma : x * z ≤ y * z | |
230 lemma = *≤ {x} {y} {z} (≤to< a) | |
231 distr-minus-* {x} {suc y} {z} | tri≈ ¬a refl ¬c = begin | |
232 minus x (suc y) * z | |
233 ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} refl-≤s ) ⟩ | |
234 0 * z | |
235 ≡⟨ sym (minus<=0 {x * z} {z + y * z} (lt {x} {z} )) ⟩ | |
236 minus (x * z) (z + y * z) | |
237 ∎ where | |
238 open ≡-Reasoning | |
239 lt : {x z : ℕ } → x * z ≤ z + x * z | |
240 lt {zero} {zero} = z≤n | |
241 lt {suc x} {zero} = lt {x} {zero} | |
242 lt {x} {suc z} = ≤-trans lemma refl-≤s where | |
243 lemma : x * suc z ≤ z + x * suc z | |
244 lemma = subst (λ k → x * suc z ≤ k ) (+-comm _ z) (x≤x+y {x * suc z} {z}) | |
245 distr-minus-* {x} {suc y} {z} | tri> ¬a ¬b c = +m= {_} {_} {suc y * z} ( begin | |
246 minus x (suc y) * z + suc y * z | |
247 ≡⟨ sym (proj₂ *-distrib-+ z (minus x (suc y) ) _) ⟩ | |
248 ( minus x (suc y) + suc y ) * z | |
249 ≡⟨ cong (λ k → k * z) (minus+n {x} {suc y} (s≤s c)) ⟩ | |
250 x * z | |
251 ≡⟨ sym (minus+n {x * z} {suc y * z} (s≤s (lt c))) ⟩ | |
252 minus (x * z) (suc y * z) + suc y * z | |
253 ∎ ) where | |
254 open ≡-Reasoning | |
255 lt : {x y z : ℕ } → suc y ≤ x → z + y * z ≤ x * z | |
256 lt {x} {y} {z} le = *≤ le | |
257 | |
258 minus- : {x y z : ℕ } → suc x > z + y → minus (minus x y) z ≡ minus x (y + z) | |
259 minus- {x} {y} {z} gt = +m= {_} {_} {z} ( begin | |
260 minus (minus x y) z + z | |
261 ≡⟨ minus+n {_} {z} lemma ⟩ | |
262 minus x y | |
263 ≡⟨ +m= {_} {_} {y} ( begin | |
264 minus x y + y | |
265 ≡⟨ minus+n {_} {y} lemma1 ⟩ | |
266 x | |
267 ≡⟨ sym ( minus+n {_} {z + y} gt ) ⟩ | |
268 minus x (z + y) + (z + y) | |
269 ≡⟨ sym ( +-assoc (minus x (z + y)) _ _ ) ⟩ | |
270 minus x (z + y) + z + y | |
271 ∎ ) ⟩ | |
272 minus x (z + y) + z | |
273 ≡⟨ cong (λ k → minus x k + z ) (+-comm _ y ) ⟩ | |
274 minus x (y + z) + z | |
275 ∎ ) where | |
276 open ≡-Reasoning | |
277 lemma1 : suc x > y | |
278 lemma1 = x+y<z→x<z (subst (λ k → k < suc x ) (+-comm z _ ) gt ) | |
279 lemma : suc (minus x y) > z | |
280 lemma = <-minus {_} {_} {y} ( subst ( λ x → z + y < suc x ) (sym (minus+n {x} {y} lemma1 )) gt ) | |
281 | |
282 minus-* : {M k n : ℕ } → n < k → minus k (suc n) * M ≡ minus (minus k n * M ) M | |
283 minus-* {zero} {k} {n} lt = begin | |
284 minus k (suc n) * zero | |
285 ≡⟨ *-comm (minus k (suc n)) zero ⟩ | |
286 zero * minus k (suc n) | |
287 ≡⟨⟩ | |
288 0 * minus k n | |
289 ≡⟨ *-comm 0 (minus k n) ⟩ | |
290 minus (minus k n * 0 ) 0 | |
291 ∎ where | |
292 open ≡-Reasoning | |
293 minus-* {suc m} {k} {n} lt with <-cmp k 1 | |
294 minus-* {suc m} {.0} {zero} lt | tri< (s≤s z≤n) ¬b ¬c = refl | |
295 minus-* {suc m} {.0} {suc n} lt | tri< (s≤s z≤n) ¬b ¬c = refl | |
296 minus-* {suc zero} {.1} {zero} lt | tri≈ ¬a refl ¬c = refl | |
297 minus-* {suc (suc m)} {.1} {zero} lt | tri≈ ¬a refl ¬c = minus-* {suc m} {1} {zero} lt | |
298 minus-* {suc m} {.1} {suc n} (s≤s ()) | tri≈ ¬a refl ¬c | |
299 minus-* {suc m} {k} {n} lt | tri> ¬a ¬b c = begin | |
300 minus k (suc n) * M | |
301 ≡⟨ distr-minus-* {k} {suc n} {M} ⟩ | |
302 minus (k * M ) ((suc n) * M) | |
303 ≡⟨⟩ | |
304 minus (k * M ) (M + n * M ) | |
305 ≡⟨ cong (λ x → minus (k * M) x) (+-comm M _ ) ⟩ | |
306 minus (k * M ) ((n * M) + M ) | |
307 ≡⟨ sym ( minus- {k * M} {n * M} (lemma lt) ) ⟩ | |
308 minus (minus (k * M ) (n * M)) M | |
309 ≡⟨ cong (λ x → minus x M ) ( sym ( distr-minus-* {k} {n} )) ⟩ | |
310 minus (minus k n * M ) M | |
311 ∎ where | |
312 M = suc m | |
313 lemma : {n k m : ℕ } → n < k → suc (k * suc m) > suc m + n * suc m | |
314 lemma {zero} {suc k} {m} (s≤s lt) = s≤s (s≤s (subst (λ x → x ≤ m + k * suc m) (+-comm 0 _ ) x≤x+y )) | |
315 lemma {suc n} {suc k} {m} lt = begin | |
316 suc (suc m + suc n * suc m) | |
317 ≡⟨⟩ | |
318 suc ( suc (suc n) * suc m) | |
319 ≤⟨ ≤-plus-0 {_} {_} {1} (*≤ lt ) ⟩ | |
320 suc (suc k * suc m) | |
321 ∎ where open ≤-Reasoning | |
322 open ≡-Reasoning | |
323 | |
324 open import Data.List | |
325 | |
326 ℕL-inject : {h h1 : ℕ } {x y : List ℕ } → h ∷ x ≡ h1 ∷ y → h ≡ h1 | |
327 ℕL-inject refl = refl | |
328 | |
329 ℕL-inject-t : {h h1 : ℕ } {x y : List ℕ } → h ∷ x ≡ h1 ∷ y → x ≡ y | |
330 ℕL-inject-t refl = refl | |
331 | |
332 ℕL-eq? : (x y : List ℕ ) → Dec (x ≡ y ) | |
333 ℕL-eq? [] [] = yes refl | |
334 ℕL-eq? [] (x ∷ y) = no (λ ()) | |
335 ℕL-eq? (x ∷ x₁) [] = no (λ ()) | |
336 ℕL-eq? (h ∷ x) (h1 ∷ y) with h ≟ h1 | ℕL-eq? x y | |
337 ... | yes y1 | yes y2 = yes ( cong₂ (λ j k → j ∷ k ) y1 y2 ) | |
338 ... | yes y1 | no n = no (λ e → n (ℕL-inject-t e)) | |
339 ... | no n | t = no (λ e → n (ℕL-inject e)) | |
340 |